2019
DOI: 10.1007/s40121-019-00273-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific Varicella-Related Complications and Their Decrease in Hospitalized Children after the Introduction of General Varicella Vaccination: Results from a Multicenter Pediatric Hospital Surveillance Study in Bavaria (Germany)

Abstract: Background: Universal varicella vaccination (UVV) for children introduced in Germany in 2004 resulted in a significant overall decline of varicella-related hospitalizations (VRHs). We investigated the incidence of specific types of varicella-related complications (VRCs) in hospitalized children and the impact of UVV on VRCs during the first 7 years of UVV. Methods: Children\ 17 years of age hospitalized with an ICD-10-based (International Classification of Diseases, 10th Revision) discharge Enhanced Digital Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, varicella can result in severe complications leading to hospitalisation and comorbidities. These can range from dehydration and skin infections to pneumonia and encephalitis [ 11 ]. It is reported that 2–6% of patients with varicella infection attending general practice develop complications [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, varicella can result in severe complications leading to hospitalisation and comorbidities. These can range from dehydration and skin infections to pneumonia and encephalitis [ 11 ]. It is reported that 2–6% of patients with varicella infection attending general practice develop complications [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…From 1999 to 2007, deaths occurred in a greater number of involved immunocompromised patients (29%) than deaths reported for immunocompetent individuals (11–18%) [ 22 ]. Although vaccination has been shown to reduce the incidence of complications and varicella-related hospitalizations overall, a German varicella surveillance project noted significantly more varicella-related complications in immunocompromised patients, including hematologic complications and systemic bacterial infections [ 23 ]. Even with vaccination becoming common practice in many countries, a systematic review of breakthrough varicella noted severe breakthrough disease in healthy and immunocompromised children [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varicella infection and complications were identified using ICD-10 codes and sorted into categories that included skin disorders, systemic bacterial infections, neurological conditions, upper and lower respiratory tract infections, ear, nose and throat conditions, musculoskeletal disorders, ophthalmic conditions and gastrointestinal disorders. Within each category, common complications associated with varicella were selected based on literature review 1,12,19–31 and further validated by clinical experts (see Table, Supplemental Digital Content 2, http://links.lww.com/INF/F400).…”
Section: Methodsmentioning
confidence: 99%
“…Varicella infection and complications were identified using ICD-10 codes and sorted into categories that included skin disorders, systemic bacterial infections, neurological conditions, upper and lower respiratory tract infections, ear, nose and throat conditions, musculoskeletal disorders, ophthalmic conditions and gastrointestinal disorders. Within each category, common complications associated with varicella were selected based on literature review 1,12,[19][20][21][22][23][24][25][26][27][28][29][30][31] Prescribed medications were classified as antivirals, antibiotics (systemic antibiotics and nonsystemic/topical antibiotics), emollients, analgesics or antihistamines, with further subgroup analysis performed for specific systemic antibiotics. Specific systemic antibiotics were selected from a list defined by the Haute Autorité de Santé of common antibiotics used for the treatment of pediatric patients with the complications included in our analysis.…”
Section: Study Measuresmentioning
confidence: 99%